On the connection between the condition of tenant farmers and the laws respecting the ownership and transfer of land in Ireland - Pim, Jonathan (Dublin Statistical Society, 1853)
Few subjects have engaged so much of the public attention in Ireland as the condition of the tenant farmers, and it is generally admitted that the present laws, and the practice generally prevailing with respect to the letting of land, have had very injurious effects in impeding the improvement of the country. Various remedies have been proposed as panaceas for these evils. Tenant-right, fixity of tenure, valuation of rent, compensation for improvements, have each had its respective advocates. Whenever the attempt has been made to reduce these proposed plans to practice as the basis of legislation, difficulties have arisen which appear not to have been previously anticipated; so that no one of these schemes, when carried out into detail, has given satisfaction to the several parties interested. The difficulties which have thus arisen, and the complicated nature of the various legislative measures proposed, naturally lead us to consider whether any of these plans are calculated to effect a cure; whether the causes of the evil do not lie deeper, and require remedies of a different character
A paper read before the Dublin Statistical Society on Wednesday, 23rd February, 1853
Keywords: Land tenure; Farming; 314.15